PKM Meningkatkan Kesiapan Siswa Menghadapi Transformasi Digital Melalui Pelatihan Manajemen Chatgpt - Sudriyanto Sudriyanto; Abdullah Farhan; Yusuf Ghozali; Moh. Khoirul Yaqin; Ivan Catur Prasetyo; Ragil Albar Fikri Putra; Moh. Rafly Islamay Pasya (Gotong Royong, 2024)
Digital transformation in education poses a significant challenge for educational institutions, including MI Al-Azhar, which still faces limitations in the digital skills of teachers and students, as well as in the integration of technology into the learning process. This community service program aims to address these issues through ChatGPT management training, designed to enhance digital skills and the ability to integrate technology into learning. The service includes intensive training for teachers and students, along with guidance on the practical application of digital technology in the classroom. The proposed solution successfully improved teachers' digital skills, with average scores increasing from 62 to 85, and students' digital literacy from 65 to 85. Additionally, there was a significant increase in technology usage, with teachers using technology in teaching rising from 20% to 90%, and students using technology in school tasks rising from 10% to 60%. The conclusion of this program indicates that ChatGPT management training is effective in addressing the challenges of digital transformation at MI Al-Azhar. Recommendations from this service include the need for ongoing support, further training, and the development of technological infrastructure to ensure the sustainability and effectiveness of technology use in learning in the future.